IDENTIFIKASI PENGGUNAAN MNDWI DALAM DINAMIKA PERUBAHAN GARIS PANTAI DI KOTA PADANG DARI TAHUN 2015-2020 - Beben Graha Putra; Arie Yulfa (JURUSAN GEOGRAFI FIS UNP, 2021)
MNDWI is a method or algorithm in remote sensing data processing, this method is efficient enough to emphasize the difference between water and urban areas. This study has 2 objectives, (1) Knowing the use of the MNDWI transformation in observing shoreline changes. (2) Monitoring the dynamics of changes in the coastline in the city of Padang in the period 2015-2020. This type of research uses quantitative research with mathematical calculations, research testing in the form of numbers using certain software and tools such as DSAS. Data collection techniques by studying literature and citing previous theories. The results of this study have 2 conclusions, namely, (1) Utilization of MNDWI transformation in observing changes in coastlines, (2) Calculation results of the average rate of change in shoreline in Padang City in 2015-2020.